TINJAUAN ASPEK KUALIFIKASI PENDIDIK, PENGUASAAN TEKNOLOGI INFORMASI DAN KOMUNIKASI, SERTA SUPERVISI AKADEMIK TERHADAP KEMAMPUAN MANAJEMEN KELAS PADA GURU SEKOLAH DASAR DI UPT PPD KECAMATAN PUNDONG KABUPATEN BANTUL - Siti Haryani (Ideguru: Jurnal Karya Ilmiah Guru, 2019)
The purpose of this study was to determine: (1) the influence of educator qualifications, the mastery of ICT, as well as academic supervision jointly against class management capabilities among elementary school teachers, (2) the effect of educator qualifications on classroom management skills in an elementary school teacher, (3) the effect of mastery of ICT on classroom management skills in an elementary school teacher, and (4) the effect academic supervision of classroom management capabilities at an elementary school teacher. This study applied the quantitative approach using the survey design. The population in this research was all elementary school teachers in UPT PPD Pundong, Bantul regency, in the academic year of 2017/2018, amounting to as much as 182 teachers distributed in 19 elementary schools. Samples in this study were 124 teachers, taken by proportional random sampling method. Data collection used questionnaires. The data analysis was conducted on the descriptive analysis, linearity and multicollinearity test, multiple regression analysis, partial correlation analysis, and donations predictors include effective contribution and relative contribution. The results showed that the educator qualifications, mastery of ICT and academic supervision simultaneously have a very significant positive influence to the ability of teachers in classroom management. It means that if educator qualifications, mastery of ICT, and academic supervision become better, the ability of teachers to manage the classroom will become better too. Partially, the educator qualifications have a very significant positive influence to the ability of teachers to manage the classroom. The mastery of ICT also has a significant positive effect on the ability of teachers in classroom management. As well as a partial academic supervision also has a very significant positive influence on the ability of teachers in classroom management. Therefore, it is necessary to improve the educator qualifications, mastery of ICT, and academic supervision to increase the ability of teachers in classroom management.